Monitoring System of Water Quality on Hydroponic Planting Media using Total Dissolved Solid (TDS) Sensor Based Arduino Uno R3 - Muhammad Hidayatullah; Sofyan Sofyan; Paris Ali Topan; Titi Andriani; Nurhairunnisah Nurhairunnisah (Jurnal Ilmu Fisika, 2022)
A water quality monitoring system in hydroponics with a Total Dissolved Solid Sensor (TDS) equipped with the Arduino UNO microcontroller has been developed.  The TDS SEN0244 sensor read the water sensitivity, which will display the value of the reading on the LCD. Furthermore, if the output is less than 2.30 Volts or 1000 ppm, the buzzer will sound once, and the dosing pump will rotate to automatically add nutrients A and B. The buzzer will sound twice if the output is more than 2.40 Volts or 1200 ppm. When reading the sensitivity of water (well water) with a water value of 400 ppm, the relevant results were obtained, namely, 1000 - 1200 ppm when 4 - 5 mL of the nutrient solution was added to water with a capacity of fewer than 6 liters. The appropriate value was obtained when testing the TDS sensor on several water samples. However, in the salt and soapy water samples, the voltage value reading was unstable or experienced an error. Implementing this system is expected to make it easier for the community, especially farmers, to cultivate hydroponic plants.